1988
DOI: 10.3109/00016488809106434
|View full text |Cite
|
Sign up to set email alerts
|

The reproducibility of caloric tests of vestibular function in young and old subjects

Abstract: The test-retest repeatability of the hot caloric response alone and of the hot and cold caloric responses combined, was evaluated in 29 subjects, over a 6-month period. The subjects were from two different age groups, 20-30 years (15 subjects) and 65-75 years (14 subjects). Intersubject variability was statistically significant in both age groups, though of greater magnitude in the older subjects. Once a vestibular caloric response baseline was established, for any given subject, there was reasonably reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Differences in caloric test method and statistical analysis of the data may explain this difference. Hajioff et al (2000) and Davidson et al (1988) described increasing variability on several ENG tests with age. One study even suggested that ENG was of little value in discriminating between healthy and dizzy elderly patients because of response variability (Hajioff, et al, 2002).…”
Section: Ces and Tesmentioning
confidence: 96%
“…Differences in caloric test method and statistical analysis of the data may explain this difference. Hajioff et al (2000) and Davidson et al (1988) described increasing variability on several ENG tests with age. One study even suggested that ENG was of little value in discriminating between healthy and dizzy elderly patients because of response variability (Hajioff, et al, 2002).…”
Section: Ces and Tesmentioning
confidence: 96%
“…Finally, Davidson and colleagues examined the reproducibility of the caloric response in 15 younger subjects (20 to 30 years) and in 14 older subjects (65 to 75 years). 81 They reported that the intersubject variability of the total caloric response was poor, citing a statistically significant intersubject variability in caloric responses in both young and older groups, with older groups exhibiting a greater magnitude of variability.…”
Section: Caloric Testingmentioning
confidence: 99%
“…It is also inexpensive, reproducible and, most importantly, can test each ear separately. 1 Because of these factors, it has become the “gold standard” in vestibular testing against which other tests are measured. There are, however, a number of limitations to caloric testing.…”
Section: Introductionmentioning
confidence: 99%